Perbandingan Tax Planning Metode Depresiasi Fix Asset dengan Kebijakan Perusahaan dalam Meminimalkan Beban Pajak Penghasilan Badan (Studi Kasus pada PT XYZ) - Zulvia Aofa; Deasy Ervina (JFAS : Journal of Finance and Accounting Studies, 2020)
Tax planning is a way to exploit a tax law gap to minimize tax expense legally, one of the ways is choosing the right method for depreciation fixed assets. This study aimed to discover tax planning in depreciation fixed assets by comparing the straight-line method and declining-balance method, the impact of profit before tax and the amount of income tax expense paid by PT XYZ. This study conducted using a qualitative approach method. The type of data used quantitative and qualitative data. The study's results showed that selecting a straight-line method has a significant impact on pressing Taxable Income and Institution Income Tax.